Promovendo o letramento visual a partir do gênero discursivo notícia de popularização da ciência - Marques, Pâmela Mariel (2015)
Multimodal texts has gained ground in our society due mainly to mobilize different semiotic resources and comply with the demand for a highly multimodal society. It is observed especially in scientific multimodal texts that resort to different semiotic resources to capture and offer different modes of meaning to the reader as images, videos, audios. However, these texts require a multimodal literacy in which the reader is able to decode and interpret critically different semiotic resources constituting a scientific multimodal text or not. For this, the school environment and teaching materials are presented as major instruments to form efficient and critic multimodal readers (ROJO, 2009), and beyond promoting scientific literacy. Thus, this study aims to verify how the textbooks have especially explored the visual semiotic resource in SP texts, a recurrent multimodal genre in English language textbooks aimed at high school. This study is based on the Critical Genre Analysis (MOTTA-ROTH, MEURER 2005 2008) and Multimodal discourse (KRESS; Van LEEUWEN, 1996/2006; JEWITT, 2003), two theoretical and methodological approaches that recognize the plurality of languages that constitute the social practices. So, 21 volumes of the seven collections of EL textbook appointed by the Ministry of education in the Guide Textbook 2012 (PNLD, 2011) were analyzed. Firstly, a survey was conducted of the units/sections on the news popularization of science in these collections. Subsequently, the identified exercises that allude to the image of the news were classified according to the stratum of language and the meaning(s) that emphasize, being these representational, interactive and compositional meanings (KRESS; van LEEUWEN, 2006). In addition, additional exercices were proposed based on these meanings and in the stratum of language. The analysis reveals that most collections presents the SP news report, but only four of them exploit the images of the news through exercises. These generally focus on pre-reading section of the analyzed activities, emphasizing the semantic and pragamatic stratum, especially the propositional content of image. In this sense, despite the high presence and occurrence of SP news report in the collections, the educational potential of the image still seems to be neglected.